Specific features of kimberlites of Mirny field (Sibirian platform) - N. N. Zinchuk; V. I. Koptil (Известия высших учебных заведений: Геология и разведка)
Results of comparative complex investigation are provided for diamonds from primary bodies of Mirny kimberlite field, among which three groups are distinguished sharply differing by typomorphic features of crystals, related with three separated in time phases of diamondiferous magmatism (I — vein A-21; II— pipes Taezhnaya and Amakinskaya; III — pipes Mir, International, XXIII-rd CPSU Congress, Dachnaya and Sputnik). For the first earliest group low content of octahedral is typical, with prevalence of individuals of rhombic dodecahedral habit; the second group is noted for approximately equal ratio of octahedral and rhombic dodecahedral habit crystals; sharp prevalence of coarse-laminar crystals of octahedral and transitive from it to rhombic dodecahedral habit is characteristic for the third group of most high-productive diatremes. Utilization of typomorphic features of crystals for reconstruction of exogenous history of diamonds on the way from primary sources to the places of modern location in placers, for paleogeographial reconstructions of ancient productive thick layers' reconstructions and clearing out directions of diamondiferous material drift, which will promote prospecting of their primary sources, has important significance.